Precipitation-site competition in duplex stainless steels: Cu clusters vs spinodal decomposition interfaces as nucleation sites during thermal aging. (1st September 2020) - Lach, Timothy G.; Frazier, William E.; Wang, Jing; Devaraj, Arun; Byun, Thak Sang
Abstract: Competing microstructural evolution mechanisms can exist simultaneously when duplex stainless steels are operating for several decades in a high temperature service environment. Such competition between different microstructural evolution pathways can be difficult to ascertain using simple model alloy systems necessitating detailed microstructural analysis of phase transformation mechanisms in complex alloys. Thus, duplex stainless steels with complex but well understood chemistries were used to investigate the relative importance of different heterogeneous nucleation sites – specifically, spinodal decomposition and Cu clustering – on Ni-Si-Mn precipitation during thermal aging. Precipitation of Ni-Si-Mn particles in ferrite-bearing steels during thermal aging and irradiation can greatly change mechanical properties. Using duplex stainless steels with custom-modified compositions along with advanced microstructural characterization and first-passage kinetic Monte Carlo simulations, it is revealed that while the interface between Cr and Fe formed during spinodal decomposition can be a pathway for solute diffusion, it is not a preferred site for Ni-Si-Mn precipitation. Instead, the presence of a higher concentration of Cu leads to the formation of small Cu-rich clusters with high energy interfaces that act as nucleation sites for Ni-Si-Mn particles. These results will inform predictive models for the use of precipitation-hardened alloys for extended operation at high temperatures. Graphical abstract: Image, graphical abstract